250 Gambaran Benigna Prostat Hiperplasia di RSUP Prof. Dr. R. D. Kandou Manado Periode Januari 2014 – Juli 2017 - Adelia, Filzha; Monoarfa, Alwin; Wagiu, Angelica (e-CliniC, 2017)
Abstract: Benign prostatic hyperplasia (BPH) is defined as stromal cell proliferation of prostate gland which causes enlargement of the gland. It manifests as urine flow disturbance, difficult to urinate, and desire to urinate, however, the urine emission is low. In 2013, Indonesia has 9.2 million cases of BPH among men aged over 60 years. This study was aimed to obtain the profile of BPH cases at Prof. Dr. R. D. Kandou Hospital Manado in the period of January 2014 to June 2017. This was a retrospective descriptive study at Medical Record Installation of Prof. Dr. R. D. Kandou Hospital. The results showed that during that period of time, the highest percentage of cases was in 2016 (38.46%) and the most common age group was 61-70 years old (46.15%). The main complaint among the patients was difficult to urinate and the most frequently performed action was transurethral resection of prostate (TURP) (51.28%). Conclusion: In this study, BPH cases were most common at the age group 61-70 years old. Moreover, TURP was the most common action performed.Keywords: benign prostatic hyperplasia Abstrak: Benigna prostat hiperplasia (BPH) didefinisikan sebagai proliferasi dari sel stromal pada prostat, yang menyebabkan pembesaran kelenjar tersebut. Manifestasi BPH dapat berupa terganggunya aliran urin, sulit buang air kecil (BAK), dan keinginan buang air kecil namun pancaran urin lemah. Pada tahun 2013 di Indonesia terdapat 9,2juta kasus BPH, umumnya diderita laki-laki berusia di atas 60 tahun. Penelitian ini bertujuan untuk mendapatkan gambaran kasus BPH di RSUP Prof. Dr. R. D. Kandou Manado periode Januari 2014 – Juli 2017. Jenis penelitian ialah deskriptif retrospektif , yang dilakukan di Instalasi Rekam Medik RSUP Prof. Dr. R. D. Kandou Manado. Hasil penelitian menunjukkan bahwa jumlah kasus BPH tertinggi pada tahun 2016 (38,46%) dan pada kelompok usia 61-70 tahun (46,15%). Keluhan utama semua pasien ialah sulit BAK. Tindakan yang paling sering digunakan yaitu transurethral resection of prostate (TURP) (51,28%). Simpulan: Kasus BPH terutama ditemukan berusia 61-70 tahun. Tindakan yang paling sering dilakukan yaitu reseksi prostat transuretra (TURP).Kata kunci: benigna prostat hiperplasia